ANALISIS PERBANDINGAN KINERJA KEUANGAN SEBELUM DAN SAAT PANDEMI COVID-19 PADA BANK DKI UNIT USAHA SYARIAH - Waskito, Meindro; Hendayana, Yayan; Maulana, Aris (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2022)
The bank's financial performance is a description of the financial condition of a certain period regarding aspects of fund raising and distribution of funds. With the Covid-19 Pandemic situation, banking financial performance is expected to continue to increase growth and maintain economic stability. Financial performance in this study was measured by ROA (Return on Assets), CAR (Capital Adequacy Ratio), NPF (Non Performing Financing), FDR (Financing to Deposit Ratio). The purpose of the study was to determine differences in the financial performance of DKI Bank Syariah Business Units before and during the Covid-19 pandemic. This research is a quantitative research. Data collection techniques in the form of library research and documentation, through the official website of the Bank DKI Sharia Business Unit, namely https://bankdki.co.id Data analysis techniques used descriptive analysis, normality test and paired sample t-test and Wilcoxon signed test. rank test which was analyzed using SPSS Software version 25. The results of this study which were analyzed using the paired sample t-test showed that there was no difference in the financial performance of Bank DKI Sharia Business Unit before and during the COVID-19 pandemic condition as measured using ROA ( Return on Assets) obtained a significance value of > 0.05 which is 0.312, NPF (Non Performing Financing) obtained a significance value of > 0.05 which is 0.109, FDR (Financing to Deposit Ratio) obtained a significance value of > 0.05 which is 0.603, for the CAR ratio (Capital Adequacy Ratio) which was analyzed using the Wilcoxon signed rank test also showed that there was no difference in financial performance before and at saaa t the condition of the covid-19 pandemic because it obtained a significance value > 0.05, which is 0.575